2021
DOI: 10.3390/app11083706
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Non-Uniform Distorted Flows, Effects on Transonic Compressor Using CFD, Regression Analysis and Artificial Neural Networks

Abstract: Non-uniform inlet flows frequently occur in aircrafts and result in chronological distortions of total temperature and total pressure at the engine inlet. Distorted inlet flow operation of the axial compressor deteriorates aerodynamic performance, which reduces the stall margin and increases blade stress levels, which in turn causes compressor failure. Deep learning is an efficient approach to predict catastrophic compressor failure, and its stability for better performance at minimum computational cost and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Furthermore, it was demonstrated that making use of GBPNN provides the highest accuracy, followed by the SVM and BPNN. In another work, Sohail et al (2021) focused on the forecasting tool of transonic compressor instability. In this regard, they utilized a dataset obtained from CFD for supervised learning of an ANN.…”
Section: Characteristics Of Axial Compressormentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was demonstrated that making use of GBPNN provides the highest accuracy, followed by the SVM and BPNN. In another work, Sohail et al (2021) focused on the forecasting tool of transonic compressor instability. In this regard, they utilized a dataset obtained from CFD for supervised learning of an ANN.…”
Section: Characteristics Of Axial Compressormentioning
confidence: 99%
“…FIGURE 3Inputs and outputs of the developed model for the compressor with distorted flow bySohail et al (2021).…”
mentioning
confidence: 99%
“…The flow field in the transonic micro-axial flow compressor's tip clearance zone was previously studied under non-uniform flow circumstances. The research focused on the negative effects of a steady-state distorted pattern of total pressure inlet flow conditions, both under-design and off-design RPM [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…NN-based controllers are proposed by Yu et al [24] to ensure steady-state spacecraft formation when in orbit. Therefore, similarly to [25], surrogate and NN models are beneficial when problems are computationally intensive and already have numerous data sets available. For the purposes of this research, the numerical calculations are not computationally intensive; therefore, the benefits of such techniques are minimized and non-gradient-and gradient-based algorithms can be directly applied.…”
Section: Introductionmentioning
confidence: 99%